Analysis of Madrasah Ibtidaiyah Teachers' Understanding of Differentiated Learning Training for Merdeka Curriculum - Lailiyah, Siti; Arrifadah, Yuni; Sadieda, Lisanul Uswah; Sutini, Sutini; Yanti, Aning Wida; Sari, Firda Mareta (Profesi Pendidikan Dasar, 2024)
Differentiated learning is crucial for addressing student diversity and ensuring all students have equal opportunities to achieve their learning objectives. Therefore, it is essential that teachers understand and implement these strategies in the classroom. This study analyzes Islamic primary school (Madrasah Ibtidaiyah/MI) teachers' understanding of differentiated learning. Using a mixed-methods approach, the research involved 54 MI teachers (10 male and 44 female) from 34 MI schools in Babat Lamongan, East Java. Instruments included written tests and interviews. The written test featured a pre-test and post-test via the Quizizz application, while interviews followed the differentiated learning training. Data analysis combined quantitative and qualitative techniques. Quantitative results showed that the MI teachers' conceptual understanding, measured by the N-gain score, was 0.078, categorizing it as low. However, qualitative findings revealed that, post-training, MI teachers demonstrated a solid understanding of all indicators: explaining concepts, identifying characteristics, providing examples and non-examples, and applying differentiated learning strategies. The study concludes that training in differentiated learning significantly enhances teachers' understanding. Regular and consistent training is recommended to sustain and further develop teachers' expertise in this area.